Quantification of tumor-derived cell free DNA(cfDNA) by digital PCR (DigPCR) in cerebrospinal fluid of patients with BRAFV600 mutated malignancies - Momtaz, Parisa; Pentsova, Elena; Abdel-Wahab, Omar; Diamond, Eli; Hyman, David; Merghoub, Taha; You, Daoqi; Gasmi, Billel; Viale, Agnes; Chapman, Paul B (Oncotarget, 2016)
Tumor-derived cell free DNA (cfDNA) can be detected in plasma. We hypothesized that mutated BRAF V600 cfDNA could be quantified in the cerebrospinal fluid (CSF) of patients with central nervous system (CNS) metastases. We collected CSF from patients with BRAF V600E or K-mutated melanoma (N=8) or BRAF V600E mutated Erdheim-Chester Disease (ECD) (N=3) with suspected central nervous system (CNS) involvement on the basis of neurological symptoms (10/11), MRI imaging (8/11), or both. Tumor-derived cfDNA was quantified by digital PCR in the CSF of 6/11 patients (range from 0.15-10.56 copies/μL). Conventional cytology was negative in all patients except in the two patients with markedly elevated levels of tumor-derived cfDNA. In 2 patients with serial measurements, CSF tumor-derived cfDNA levels reflected response to treatment or progressive disease. CSF tumor-derived cfDNA has the potential to serve as a diagnostic tool that complements MRI and may be more sensitive than conventional cytology.